Analisis Penerimaan Pengguna Aplikasi Kitabisa Menggunakan Model UTAUT-3 - Hilyah, Agna; Shiddieq, Diqy Fakhrun; Lestari, Nurfarahim Sugih; Susilawati, Wati (STMIK Banjarbaru, 2024)
One fintech initiative, crowdfunding, is playing a role in transforming the funding process. A popular crowdfunding application in Indonesia is Kitabisa. The growth of online donations on the Kitabisa platform increases every year, so it is necessary to analyze more deeply the adoption of user acceptance of the Kitabisa application. Therefore, this study aims to provide an understanding of the user acceptance of the Kitabisa application through the UTAUT-3 framework, which has the variables Performance Expectancy, Effort Expectancy, Facilitating Conditions, Social Influence, Hedonic Motivation, Habit, Price Value, and Personal Innovativeness. The Price Value variable is not used because Kitabisa is a philanthropic application that does not involve additional costs for its users. quantitative methods, involving 103 users who were collected through questionnaires using Likert scale assessments and analyzed by the SEM-PLS method using SmartPLS 3.0 tools. The results found, Behavior Intention and Habit significantly affect Use Behavior, Habit and Personal Innovativeness affect Behavior Intention. In contrast, other variables were not found to have an influence in this study.Kata kunci: Crowdfunding; Kitabisa; UTAUT-3; SEM-PLSÂ AbstrakSalah satu inisiatif Fintech, crowdfunding yang memainkan peran dalam mengubah proses pendanaan. Aplikasi crowdfunding yang populer di Indonesia adalah Kitabisa. Pertumbuhan donasi online pada platform Kitabisa meningkat setiap tahunnya, sehingga perlu dianalisis lebih lanjut terkait adopsi penerimaan pengguna aplikasi Kitabisa. Oleh karena itu, Penelitian ini bertujuan untuk memberikan pemahaman mengenai penerimaan pengguna aplikasi Kitabisa melalui kerangka kerja UTAUT-3 yang memiliki variabel Performance Expectancy, Effort Expectancy, Facilitating Conditions, Social Influence, Hedonic Motivation, Habit, Price Value, dan Personal Innovativeness. Variabel Price Value tidak digunakan karena Kitabisa sebagai aplikasi filantropi yang tidak melibatkan biaya tambahan bagi penggunanya. Dengan metode kuantitatif, melibatkan 103 pengguna yang dihimpun melalui kuesioner menggunakan penilaian skala Likert dan dianalisis dengan metode SEM-PLS menggunakan tools SmartPLS 3.0. Hasil penelitian ditemukan, Behavior Intention dan Habit berpengaruh terhadap Use Behavior, Habit serta Personal Inovativeness berpengaruh terhadap Behavior Intention. Sebaliknya, variabel lainnya tidak ditemukan pengaruh pada penelitian ini.Â